Tafakur Pandemi Covid-19: Telaah Perspektif Pendidikan Islam - Mardeli Mardeli; Lola Fadilah; Ratih Novianti; Juwita Puspita Sari; Zulhijar Zulhijar; Sukirman Sukirman (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Since being confirmed at the end of 2019, the covid-19 pandemic has caused a fairly high death toll and caused widespread panic around the world. This study aims to understand and deal with the covid-19 pandemic from the perspective of Islamic education and it is hoped that solutions will be found in dealing with this covid-19 pandemic. The research method used is library research because the data sources come from books and other written documents. The results of this study indicate that from the point of view of Islamic education, the way to deal with the covid-19 pandemic is to pray, namely to always ask for protection and help from Allah SWT by always praying and worshiping, keeping the rows apart when praying, doing activities at home, one of which is a learning system. online, maintaining food hygiene, namely by always paying attention to food hygiene and paying attention to a healthy lifestyle, curative efforts, namely taking treatment when exposed to covid-19 by taking treatment at the hospital, taking medication, self-isolation, rest and drinking lots of water. This is done to reduce the spread of covid-19.